Polish Archaisms against their Equivalents in Bulgarian - Sotirov, Petar (Slavistica Vilnensis, 2022)
The subject are Polish archaic words whose equivalents are in active use in modern Bulgarian. The aim is to reveal the composition of this group of archaisms and to show the main reasons that led to the Polish-Bulgarian asymmetry in terms of archaism. The conducted research shows that about 140 lexemes that have been archaized in Polish are present in Bulgarian. Among them, lexical and semantic archaisms prevail, while archaic words are in a smaller number. The thematically studied archaisms belong mainly to categories related to human, for example, to physical and mental characteristics, to everyday life or to interpersonal relations. By origin, archaisms are both native and borrowed words. From a formal point of view, Polish archaic words and their modern Bulgarian counterparts are identical, with minimal or more divergence. From the point of view of semantics, most Polish-Bulgarian lexical pairs have the same meaning, there are also pairs with a greater or lesser meaning divergence consisting in broadening or narrowing the semantics of the Bulgarian word compared to the Polish one. The reasons that contributed to the occurrence of the Polish-Bulgarian asymmetry in the field of the archaization of lexis are not strictly linguistic in nature, but represent the social, historical and political aspect of the language. They reflect the way in which scientific terminology was developed, social attitudes towards influences from foreign languages, the specificity of social relations and the process of shaping the standard language in both countries.